Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 463: 103



Work Step by Step

$-36x^{3}y+62x^{2}y^{2}-12xy^{3}\qquad$...factor out the common term, $-2xy$. $=-2xy(18x^{2}-31xy+6y^{2})$ ... Searching for two factors of $ac=108$ whose sum is $b=-31,$ we find$\qquad-4$ and $-27.$ Rewrite the middle term and factor in pairs: $=-2xy(18x^{2}-4xy-27xy+6y^{2})=$ $=-2xy[2x(9x-2y)-3y(9x-2y)]$ =$-2xy(9x-2yb)(2x-3y)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.